New development plan of Turkey (2014-2018) and old institutional problems: lessons from Poland - Özbek, Oğuz (Nowy plan rozwoju Turcji (2014-2018) i stare problemy instytucjonalne: lekcje z Polski, 2016)
This paper concerns the institutional tools of the Tenth Development Plan of Turkey (2014- -2018) in a critical way through a comparison between the regional development practices of Turkey and Poland. The Tenth Plan introduced in 2014 considerably rests on the strategic framework of the preceding Ninth Development Plan (2007-2013). The main topics of the institutional analysis in the paper involve new institutional bodies and governance, new and old policy tools of development planning and sustainable development and territorial statistical system. Here, the key lesson derived from the Polish case, especially from Lower Silesia, is that the policy tools of a regional development framework at national level (development plan) can only be operational and effective when these tools retain functional ties to the real economy and catch the creative essence of development. In that vein, the paper makes a comparison between Turkey and Poland by highlighting the policy tools of current regional development practices and strategies in Poland. These tools are related to the emerging learning economy, supporting institutions, growth pole strategy, urbanization economies, entrepreneurship, regional innovation strategies, metropolitan administration and public-private partnership in Poland
Biblioteka Regionalisty, 2016, Nr 16, s. 75-86
Keywords: Turkey; Poland; development planning; regional area; institutions; Turcja; Polska; planowanie rozwoju; obszar regionalny; instytucje